A novel human embryonic stem cell‐derived Huntington's disease neuronal model exhibits mutant huntingtin (mHTT) aggregates and soluble mHTT‐dependent neurodegeneration. Issue 5 (16th January 2013) - Lu, Boxun; Palacino, James
Abstract : Most neurodegenerative diseases are linked to aberrant accumulation of aggregation‐prone proteins. Among them, Huntington's disease (HD) is caused by an expanded polyglutamine repeat stretch in the N terminus of the mutant huntingtin protein (mHTT), which gets cleaved and aggregates in the brain. Recently established human induced pluripotent stem cell‐derived HD neurons exhibit some disease‐relevant phenotypes and provide tools for HD research. However, they have limitations such as genetic heterogeneity and an absence of mHTT aggregates and lack a robust neurodegeneration phenotype. In addition, the relationship between the phenotype and mHTT levels has not been elucidated. Herein, we present a human embryonic stem cell (hESC)‐derived HD neuronal model expressing HT‐Texon1 fragments, which addresses the deficiencies enumerated above. The wild‐type and HD lines are derived from an isogenic background and exhibit insoluble mHTT aggregates and neurodegeneration. We also demonstrate a quantitative relationship between neurodegeneration and soluble monomeric (but not oligomeric or aggregated) mHTT levels. Reduction of ~10% of mHTT is sufficient to prevent toxicity, whereas ~90% reduction of wild‐type HTT is safe and well‐tolerated in these cells. A known HD toxicity modifier ( Rhes ) showed expected rescue of neurodegeneration. Therefore, the hESC‐derived neuronal models complement existing induced pluripotent stem cell‐derived neuronal models and provide valuable tools for HD research.—Lu, B., Palacino, J. A novel human embryonic stem cell‐derived Huntington's disease neuronal model exhibits mutant huntingtin (mHTT) aggregates and soluble mHTT‐dependent neurodegeneration. FASEB J. 27, 1820–1829 (2013). www.fasebj.org